Nutrient-rich submarine groundwater discharge increases algal carbon uptake in a tropical reef ecosystem - La Valle, Florybeth Flores; Jacobs, Julian M.; Thomas, Florence I.; Nelson, Craig E. (Frontiers in Marine Science, 2023)
Submarine groundwater discharge (SGD) in high volcanic islands can be an important source of freshwater and nutrients to coral reefs. High inorganic nutrient content is generally thought to augment primary production in coastal systems but when this is delivered via a freshwater vector as is the case with SGD in this study, the effects on productivity are unclear. In the current literature, there is limited evidence for a direct association between SGD and primary productivity of reefs. To elucidate the response of primary productivity to SGD, we conducted spatially and temporally explicit in situ benthic chamber experiments on a reef flat along a gradient of SGD. We found significant quadratic relationships between C-uptake and SGD for both phytoplankton and the most abundant macroalga, Gracilaria salicornia, with uptake maxima at SGD-derived salinities of 21−22 (24.5−26.6 μmol NO3-L−1). These results suggest a physiological tradeoff between salinity tolerance and nutrient availability for reef primary producers. Spatially explicit modeling of reefs with SGD and without SGD indicate reef-scale G. salicornia and phytoplankton C-uptake decreased by 82% and 36% in the absence of SGD, respectively. Thus, nutrient-rich and low salinity SGD has significant effects on algal C-uptake in reef systems.